MAKING ARROWS FROM WOOD BASIC MATERIALS TO INCREASE SKILLS OF KUALA GEULUMPANG KECAMATAN JULOK EAST ACEH DISTRICT - Dodi Irwansyah; Suandi Selian (Global Science Society, 2019)
The Provinces of Aceh and North Sumatra (North Sumatra) Officially registered as potential hosts with the National Sports Week (PON) in 2024, East Aceh District, especially the district of Julok, there were already human resources who were able to make arrows from paralon pipes, the ability of youth in the julok district was obtained from the community service that is carried out by langsa ocean university lecturers in 2017, by doing so in this advanced PKM we will provide skills to make money from cash. The problems found in the area are the youth of Julok sub-district. In particular, Kuala Geulumpang village has been able to make arrows, but the melum is able to make Arrow, this PKM is planned to run for three months starting from July to September 2018, located in kuala geulumpang village, district Aceh Timur, with a total of 10 participants, this PKM draft consists of collecting supporting data for the implementation of community service for 3 weeks,